2000
DOI: 10.1002/(sici)1097-0142(20000315)88:6<1470::aid-cncr27>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between age at the time of radiation exposure and extent of disease in cases of radiation-induced childhood thyroid carcinoma in Belarus

Abstract: BACKGROUND Increased incidence of childhood thyroid carcinoma, particularly in the youngest children, has been reported from Belarus since the nuclear reactor accident at Chernobyl in 1986. The relation between disease severity and age at the time of the accident, not previously established in this cohort, was analyzed in this study. METHODS The authors studied the association between disease severity, expressed by TNM classification, and age at radiation exposure in a cohort of 483 patients younger than 8 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 20 publications
0
30
1
4
Order By: Relevance
“…The observations on the extent of invasion and the development of peritumour fibrosis support this; the short latency tumours show a higher level of both intra-and extrathyroid invasion than the long latency group, while the long latency group shows a significantly greater development of peritumour fibrosis, usually associated with less-aggressive tumours. In addition, clinical studies showed that tumours with a long latent period were less aggressive (Farahati et al, 2000), although screening could have been relevant, and the study was not controlled for age at exposure. Unfortunately, it was not possible to carry out direct analysis of cells in cycle or of the molecular biology in all of the tumours in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The observations on the extent of invasion and the development of peritumour fibrosis support this; the short latency tumours show a higher level of both intra-and extrathyroid invasion than the long latency group, while the long latency group shows a significantly greater development of peritumour fibrosis, usually associated with less-aggressive tumours. In addition, clinical studies showed that tumours with a long latent period were less aggressive (Farahati et al, 2000), although screening could have been relevant, and the study was not controlled for age at exposure. Unfortunately, it was not possible to carry out direct analysis of cells in cycle or of the molecular biology in all of the tumours in our study.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, it is known from animal studies that the risk of developing thyroid carcinoma is increased after long-lasting, elevated thyrotropin concentrations, especially after exposure to radiation. 8 For this reason, although solid evidence in humans is lacking, correcting thyrotropin elevation after exposure to radiation often is advised.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Furthermore, thyroid tissue in children appears to be more radiosensitive than in adults, [15][16][17] and children with neuroblastoma may even be more susceptible to radiation effects on this gland compared with children who have other malignancies. 18 To protect the thyroid against these adverse radiation effects, it is common practice to administer excessive amounts of potassium iodide during exposure to radioiodide.…”
mentioning
confidence: 99%
“…X55068). The amplified products were labeled using 2.4 ACi of [a 33 -P]dCTP (Amersham Biosciences, Buckinghamshire, England) and 2.5 units of Taq polymerase were used in the PCR reaction. The BAT-40 primers were 5V-AATAACTTCCTACACCACAAC-3V (4,7,2V,4V,5V,7V -hexachloro-6-carboxyfluorescein-labeled) and 5V-GTAGAGCAA-GACCACCTT-3V (39), which amplify a 126-bp product containing the standard 40 A repeat, according to the sequence of the HSD3B1 gene (Genbank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…Association studies to identify genetic risk factors to cancer are just emerging (29)(30)(31)(32). Related to thyroid cancer risk, few studies have been reported, mostly referring to environmental factors (33)(34)(35)(36)(37). Consequently, although specific genotypes associated with thyroid cancer risk have not yet been described; as in other common cancers, the importance of genetic variants to the risk of sporadic thyroid cancer might be expected.…”
Section: Introductionmentioning
confidence: 99%